Pharmacological manipulation of arachidonic acid-epoxygenase results in divergent effects on renal damage - Li, Jing; Stier, Charles T.; Chander, Praveen N.; Manthati, Vijay L.; Falck, John R.; Carroll, Mairéad A. (Frontiers in Pharmacology, 2014)
Kidney damage is markedly accelerated by high-salt (HS) intake in stroke-prone spontaneously hypertensive rats (SHRSP). Epoxyeicosatrienoic acids (EETs) are epoxygenase products of arachidonic acid which possess vasodepressor, natriuretic, and anti-inflammatory activities. We examined whether up-regulation (clofibrate) or inhibition [N-methylsulfonyl-6-(2-propargyloxyphenyl)hexanamide (MS-PPOH)] of epoxygenase would alter systolic blood pressure (SBP) and/or renal pathology in SHRSP on HS intake (1% NaCl drinking solution). Three weeks of treatment with clofibrate induced renal cortical protein expression of CYP2C23 and increased urinary excretion of EETs compared with vehicle-treated SHRSP. SBP and urinary protein excretion (UPE) were significantly lowered with clofibrate treatment. Kidneys from vehicle-treated SHRSP, which were on HS intake for 3 weeks, demonstrated focal lesions of vascular fibrinoid degeneration, which were markedly attenuated with clofibrate treatment. In contrast, 2 weeks of treatment with the selective epoxygenase inhibitor, MS-PPOH, increased UPE without significantly altering neither urinary EET levels nor SBP. Kidneys from vehicle-treated SHRSP, which were on HS intake for 11 days, demonstrated occasional mild damage whereas kidneys from MS-PPOH-treated rats exhibited widespread malignant nephrosclerosis. These results suggest that pharmacological manipulation of epoxygenase results in divergent effects on renal damage and that interventions to increase EET levels may provide therapeutic strategies for treating salt-sensitive hypertension and renal damage.